Changes of gut microbiota and tricarboxylic acid metabolites may be helpful in early diagnosis of necrotizing enterocolitis: A pilot study - Du, Ting-Ting; Liu, Xiao-Chen; He, Yu; Gao, Xiong; Liu, Zhen-Zhen; Wang, Zheng-Li; Li, Lu-Quan (Frontiers in Microbiology, 2023)
Purpose We aimed to explore the value of gut microbiota and tricarboxylic acid (TCA) metabolites in early diagnosis of necrotizing enterocolitis (NEC) among infants with abdominal manifestations. Methods Thirty-two preterm infants with abdominal manifestations at gestational age ≤34 weeks were included in the study and were divided into non-NEC (n=16) and NEC (n=16) groups. Faecal samples were collected when the infants were enrolled. The gut microbiota was analysed with high-throughput sequencing, and TCA metabolites were measured with multiple reaction monitoring (MRM) targeted metabolomics. Receiver operating characteristic (ROC) curves were generated to explore the predictive value of the obtained data. Results There was no significant difference in alpha diversity or beta diversity between the two groups (P>0.05). At the phylum level, Proteobacteria increased, and Actinomycetota decreased in the NEC group (P<0.05). At the genus level, Bifidobacterium and Lactobacillaceae decreased significantly, and at the species level, unclassified Staphylococcus, Lactobacillaceae and Bifidobacterium animalis subsp. lactis decreased in the NEC group (P<0.05). Further Linear discriminant analysis effect sizes (LEfSe) analysis showed that the change in Proteobacteria at the phylum level and Lactobacillaceae and Bifidobacterium at the genus level scored higher than 4. The concentrations of succinate, L-malic acid and oxaloacetate in the NEC group significantly increased (P<0.05), and the areas under the ROC curve for these metabolites were 0.6641, 0.7617 and 0.7344, respectively. Conclusion Decreased unclassified Staphylococcus, Lactobacillaceae and Bifidobacterium animalis subsp. lactis at the species level as well as the increase in the contents of some TCA metabolites, including succinate, L-malic acid and oxaloacetate, have potential value for the early diagnosis of NEC.